Investigation of the Influence of Skewed Slots and Degmagnetization Effects to Line Start Permanent Magnet Assistance Synchronous Reluctance Motors - Manh, Tien Ho; Minh, Dinh Bui; Minh, Tu Pham; Quoc, Vuong Dang (Engineering, Technology & Applied Science Research, 2023)
A permanent magnet assistance synchronous reluctance motor can start directly with a net voltage or a power converter via a torque control method. However, this motor has usually a higher irreversible demagnetization level in comparison with interior permanent magnet motors, due to the fewer permanent magnets in rotor slots. In order to cope with this disadvantage, different arrangements of permanent magnets in the rotor of the line-start permanent magnet assistance synchronous reluctance motor are proposed in this paper. The V magnet shape taking skewed slots and demagnetization effect into account with the short circuit current are investigated by the finite element approach. The efficiency, torque, and output power of the proposed model have been also improved. Finally, the rotor with 3V layered magnets is prototyped to verify the efficiency of the proposed motor.